Integrating public art in Malaysian urban landscape - Hasna, Mohd Fabian (2012)
The need of public to have a better quality urban living environment, urging this country to have a better urban retreat places. As Malaysia blessed with rich cultural patterns, art approach may be one of the components to be blended in this area. Public art can be in the form of sculpture, mural, fountain and even stabile or mobile inside shopping mall. From the global perspective, its existence breaks the mundane environment and generates some kind of positive social flux towards public spaces. The sustainability of public art breathes upon the fusion of site, art and public as one organization. However public art in Malaysia did not function as it should be, hence, exposed the lack of integration of public art in urban landscape. In this study, it is shown that public art can be integrated in the Malaysia urban landscape. The particular focus of this research is on investigating the potential and problems of public art in Malaysia urban landscape. Interview with selected respondents such as academician, landscape architect, local authority, artist and art organization and observation was done to justify this matter. The data then will be analyse in qualitative approach and triangulation method as validation approach. The first part of the study examined public art as a contributor towards quality urban living environment. Subsequently, attention highlights more on the issues and problems that shielding the Malaysia urban landscape to be fitted with public art. It is anticipated to create the awareness of the possibilities of integrating public art in Malaysian urban landscape. It is also give some changes or added value in the public art development in Malaysia especially in urban landscape.